The Early Days of the COVID-19 Pandemic: Clinical Features and Findings of the Chest Radiograph of the Patients in the East Coast of Malaysia - Yu Kuan, Justin Tan; Fouzi, Liyana Ahamad; Razali, Norhaya Mohd; Meng, Teoh Kok; Ab Rahman, Ahmad Kashfi; Aziz, Zariah Abdul; Mohd Nasir, Mohd Nazri; Wan Ibrahim, Wan Zulkafli; Sidek, Norsima Nazifah (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: The use of chest radiographs in managing COVID-19 is more practical than computed tomography scan in Malaysia, because of its limited resources. Objective: To describe chest x-ray (CXR) characteristics and relevant parameters in COVID-19 patients. Methods: This is a retrospective study of 98 COVID-19 cases admitted to general hospital in Terengganu, Malaysia. CXRs of these patients were reviewed to describe the features and distribution of the abnormalities. Clinical characteristics and laboratory parameters were extracted from the electronic medical records. Results: The mean age was 42 (17). Forty-four (45%) patients had co-morbidity; the commonest were hypertension (29%) and diabetes mellitus (14%). Sixty-seven (68%) cases were symptomatic. The most common symptoms were fever (42%) and cough (45%). The mean ALC was 2.39×109/L (0.81) and mean CRP 17.51 mg/L (55.94). CXR abnormalities were detected in 37 patients (38%) which include interstitial opacity in 21 (57%) patients, consolidation in 17 (46%) patients, and ground-glass opacities 12 (32%). These changes predominantly distributed bilaterally (19 [51%] of cases), located at the lower zones (49%) and peripherally (51%). Total mean score for CXR severity was 2.43 (1.48) and the mean CXR severity score for each clinical staging was found to be increasing with the advancing clinical stage of the disease. Conclusion: CXR features described here were in line with previous publications on COVID-19 CXR findings. Patients with mild to moderate staging may not have low ALC or increased CRP levels. CRP was increased in patients with advanced clinical staging. International Journal of Human and Health Sciences Vol. 07 No. 03 Jul’23 Page: 244-251